Switchable printed antenna for wideband-narrowband application - Taat, Afifah (2014)
Recently, the multi-mode application that consists of wideband system or UWB wideband-narrowband configuration have been reported as an important device for future wireless communication system such as Cognitive Radio (CR). This application has the capability of sensing which need wideband frequency and at the same time provides locking system at the specific frequency band, namely narrowband application. Many conventional antennas do not provide such advantage. Thus in this thesis, a compact and low cost switchable printed antenna with combination of wideband and narrowband into single antenna is proposed. This switchable antenna is integrated with PIN diode switches to change the frequency that can operate for several modes. The proposed antennas are designed to operate from 3.5GHz until 14GHz. There are four different structures of circular printed antenna with have different capabilities that have been proposed. The antennas consist of slotting and radiating element in both sides which acts as complementary of each other. From the third structure of proposed antenna, the effects of ground plane have been investigated. The frequency range becomes wideband when the size of the ground plane is around 14.5mm. In general, the width of the ground will have significant impact on the resonant frequency. There are two strips of ground plane that are separated by a gap of 0.5mm and connected by three pin diode switches. The antenna successfully operates for UWB application (3.2GHz to 13.6GHz) when all of the switches labelled as S1, S2 and S3 are in ON state. Besides, in this work, a stub technique is approached to change the wideband into narrowband by adding these stubs, the antenna provides a frequency band at 2.4GHz (narrowband), 6.7GHz (narrowband) and 3.2GHz-13.6 (wideband) respectively.